Screening of Mycobacterium avium subsp. paratuberculosis mutants for attenuation in a bovine monocyte-derived macrophage model - Lamont, Elise A.; Talaat, Adel M.; Coussens, Paul M.; Bannantine, John P.; Grohn, Yrjo T.; Katani, Robab; Li, Ling-ling; Kapur, Vivek; Sreevatsan, Srinand (Frontiers in Cellular and Infection Microbiology, 2014)
Vaccination remains a major tool for prevention and progression of Johne’s disease, a chronic enteritis of ruminants worldwide. Currently there is only one licensed vaccine within the United States and two vaccines licensed internationally against Johne’s disease. All licensed vaccines reduce fecal shedding of Mycobacterium avium subsp. paratuberculosis (MAP) and delay disease progression. However, there are no available vaccines that prevent disease onset. A joint effort by the Johne’s Disease Integrated Program (JDIP), a USDA-funded consortium, and USDA- APHIS/VS sought to identify transposon insertion mutant strains as vaccine candidates in part of a three phase study. The focus of the Phase I study was to evaluate MAP mutant attenuation in a well-defined in vitro bovine monocyte-derived macrophage (MDM) model. Attenuation was determined by colony forming unit (CFUs) counts and slope estimates. Based on CFU counts alone, the MDM model did not identify any mutant that significantly differed from the wild-type control, MAP K-10. Slope estimates using mixed models approach identified six mutants as being attenuated. These were enrolled in protection studies involving murine and baby goat vaccination-challenge models. MDM based approach identified trends in attenuation but this did not correlate with protection in a natural host model. These results suggest the need for alternative strategies for Johne’s disease vaccine candidate screening and evaluation.